The effect of a balance training program with and without mirror on postural control of lower limb amputees - Mohamadtaghi, M.; Hejazidinan, P.; Shamsipourdehkordi, P.; Saemi, E. (International Journal of Applied Exercise Physiology, 2018)
Objectives. The aim of the present study was to compare the effect of a selected balance program with and without using mirror on balance of individual with amputee. Methods. Twenty-one lower limb amputees participated in this study and randomly were recruited into three groups: control, balance program, and mirror balance program. To asses postural control, Computerized Dynamic Posturography was used Using sensory organization test, balance was measured in six conditions (first: existence of sight, hearing and proprioception; second: elimination of sight; third: manipulation of vestibular system; fourth: manipulation of proprioception; fifth: elimination of sight and manipulation of proprioception and sixth: manipulation of vestibular system and proprioception). Results. The results indicated that the stability score in both balance and mirror balance groups have improved compare to the control group. Furthermore, in the first and second conditions, both experimental groups have obtained a higher stability score and a less displacement in the center of gravity compare to the control. In the sixth condition, the stability score was lower and displacement score was higher. Also, the amputee in the balance exercise using mirror group had a better balance in all the six conditions. Conclusion. Finally, we can conclude that undergoing a series of balance exercises with and without mirror improves balance and postural stability in lower limb amputee.